The Jewish dialogue with Greece and Rome : studies in cultural and social interaction - Rajak, Tessa, 1946- (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 2001)
Twenty-seven interdisciplinary essays on aspects of Judaism in the Greco-Roman world, exemplifying a wide range of techniques, by a well-known scholar. Three are previously unpublished, including a reappraisal of the Judaism and Hellenism debate and a study of the Sardis synagogue. The book's overall coherence derives from the author's long-standing interests in the analysis of texts as documents of cultural and religious interaction, and in how Jewish communities were woven into the social fabric of Greek cities in the Hellenistic and Roman East. The four sections are: Greeks and Jews, Josephus, The Jewish Diaspora and Epigraphy, and finally Beyond the Greeks and Romans, essays which extend into Christian literature and on to the nineteenth century reception of the Judaism/Hellenism dichotomy. Scholars and students from a wide variety of backgrounds will benefit. This publication has also been published in paperback, please click here for details.